From Resilience to Burnout: Psychological Features of Italian General Practitioners During COVID-19 Emergency - Di Monte, Cinzia; Monaco, Silvia; Mariani, Rachele; Di Trani, Michela (Frontiers in Psychology, 2020)
During the COVID-19 pandemic in Italy, General Practitioners (GPs) are ensuring continued access to primary care for citizens, while also absorbing more of the impact of the crisis than most professional groups. The aim of this study is to explore the relationships between dimensions of burnout and various psychological features among Italian GPs during COVID-19 emergency. A group of 102 GPs completed self-administered questionnaires available online through Google Forms, including: Maslach Burnout Inventory (MBI); Resilience Scale; Intolerance of Uncertainty Scale Short Form (IU); Coping Inventory for Stressful Situations (CISS). Cluster analysis highlighted four distinct burnout risk profiles: Low Burnout, Medium Risk, High Risk, and High Burnout. The High Burnout group showed both lower Resilience and lower CISS Task-oriented coping strategy than the Medium Risk group, and higher IU Prospective than the Low Burnout group. Results of a linear regression analysis confirmed that CISS Emotion-oriented style positively predicted MBI Emotional Exhaustion; CISS Task-oriented and Emotion-oriented emerged as significant predictors (negatively and positively, respectively) of MBI Depersonalization; and Resilience positively predicted MBI Personal Accomplishment. In conclusion, the results showed that the COVID-19 emergency has had a significant impact on GPs work management. Implementing task-oriented problem management, rather than emotional strategies, appears to protect against burnout in these circumstances. It is possible that the emotions related to the pandemic are too intense to be regulated and used productively to manage the professional issues that COVID-19 pandemic presents.